(untitled) - Novalis, Susann (San Francisco, 1999)
Access 2000 is here, and never has the power of Access depended so much on VBA programming. This makes the Access 2000 VBA Handbook essential reading if you want to use Microsoft's popular database product to its full advantage. If you're an Access user, you'll benefit from step-by-step coverage of VBA basics that will simplify your work. If you're a developer, you'll master the high-end techniques introduced in the latest release-so you can stay on top of your job.
Keywords: Database management,Quản trị cơ sở dữ liệu